1986
DOI: 10.2355/isijinternational1966.26.503
|View full text |Cite
|
Sign up to set email alerts
|

Increase in low-temperature reduction degradation of iron ore sinter due to hematite-alumina solid solution and columnar calcium ferrite.

Abstract: SynopsisDirect observation of lattice images by TEM of magnetite reduced f rom hematite made clear ultramicroscopic partial distortion due to solid solution o f A12O3. Furthermore, the effect o f solid solution of A12O3 with hematite on strain of magnetite, which had reduced grains of the hematite with a mixture gas of CO C02, was estimated by line-broadenings of peaks of X-ray diffraction. It revealed that increasing amounts o f A12O3 increased the strain of magnetite.Fracture strength of the minerals in sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…8(1-C). A number of other authors [30][31][32] have reported that volume expansion will occur during the reduction of this kind of SH, which would adversely affect the low-temperature reduction disintegration of sinter. This volume expansion is mainly due to the rapid cooling of the surface of the sinter cake making the transition of the Fe 2 O 3 phase incomplete.…”
Section: Microstructure Observationmentioning
confidence: 99%
“…8(1-C). A number of other authors [30][31][32] have reported that volume expansion will occur during the reduction of this kind of SH, which would adversely affect the low-temperature reduction disintegration of sinter. This volume expansion is mainly due to the rapid cooling of the surface of the sinter cake making the transition of the Fe 2 O 3 phase incomplete.…”
Section: Microstructure Observationmentioning
confidence: 99%
“…5) Other ferrite phases observed in industrial sinters include monocalcium ferrite, CaO. 6) SFCA phases are believed to be the most desirable bonding phases in iron ore sinter because of their high reducibility, 7) high mechanical strength and low reduction degradation, 8,9) all of which are significant factors in determining the productivity and efficiency of the blast furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, particularly in Japan, it is strongly believed that the secondary hematite, also known as skeletal rhombohedral hematite, is the major cause of poor reduction degradation resistance of sinter. 15,38) This is based on frequent observations of cracks around the narrow neck regions of such hematite. However, low to intermediate levels of alumina have been reported to reduce the amount of secondary hematite and increase SFCA in the sinter structure, both of which should be advantageous to RDI.…”
mentioning
confidence: 99%